The amount of mandibular setback influence on occlusal force following sagittal split ramus osteotomy. Issue 9 (November 2015) - Moroi, Akinori; Yoshizawa, Kunio; Iguchi, Ran; Ikawa, Hiroumi; Kosaka, Akihiko; Hotta, Asami; Tsutsui, Takamitsu; Saida, Yuriko; Ueki, Koichiro
Abstract: Purpose: The purpose of this study was to examine the influence between the magnitude of setback in sagittal split ramus osteotomy (SSRO) and occlusal contact area and bite force without relapse after surgery. Patients and methods: Sixty female patients with a diagnosis of mandibular prognathism were divided into 3 groups according to the magnitude of setback: group 1 (≤5 mm), group 2 (>5 mm but <10 mm), and group 3 (≥10 mm). All patients underwent skeletal analysis by lateral and frontal cephalogrammetry and measured the occlusal contact area and bite force by the pressure-sensitive system (Dental Prescale, Dental Occlusion Pressuregraph FDP-705; Fuji Photo Film Co., Tokyo, Japan) preoperatively and postoperatively at 1 month, 3 months, 6 months, and 1 year. Results: There were no significant differences in occlusal contact area and bite force between the 3 groups. Only group 3 showed a significant difference in occlusal contact area and bite force between the preoperative and 1-year measurements. Conclusion: The results indicate that the magnitude of setback did not influence the bite force or occlusal contact area in SSRO.